Frequency of consumption of fruits, vegetables and soft drinks: a comparative study among adolescents in urban and rural areas - Iza Cristina de Vasconcelos Martins Xavier; Carla Menêses Hardman; Maria Laura Siqueira de Souza Andrade; Mauro Virgilio Gomes de Barros (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
Objective: To compare the frequency of consumption of fruits, vegetables and soft drinks among adolescents living in urban and rural areas of Pernambuco State. Methods: A cross-sectional study based on secondary analysis of data from a representative sample of high school students in Pernambuco (n = 4,207, 14 - 19 years) was conducted. Data were collected through a previously validated questionnaire. Adolescents who reported a daily consumption of soft drinks and occasional consumption of fruits, juices and vegetables were classified as exposed to inadequate standard of consumption of these foods. The independent variable was the place of residence (urban/rural). Data were analyzed by frequency distribution, χ2 test and binary logistic regression. Results: It was observed that students residing in rural areas had a higher prevalence of occasional consumption of natural fruit juices (37.6%; 95%CI 36.1 - 39.0) than those living in urban areas (32.1%; 95%CI 30.7 - 33.6). The proportion of students exposed to daily consumption of soft drinks was higher among those who reported they lived in urban areas (65.0%; 95%CI 63.5 - 66.4) compared to those who reported living in rural areas (55.3%; 95%CI 53.8 - 56.9). Conclusion: Adolescent students living in rural areas had a higher prevalence of low consumption of natural fruit juices while those residing in urban areas had a higher prevalence of daily consumption of soda drinks.